2014
DOI: 10.3233/ais-140255
|View full text |Cite
|
Sign up to set email alerts
|

An approach to develop intelligent learning environments by means of immersive virtual worlds

Abstract: Merging Immersive Virtual Environments, Natural Language Processing and Artificial Intelligence techniques provides a number of advantages to develop Intelligent Environments for multiple applications. This paper is focused on the application of these technologies to develop intelligent learning environments. Education is one of the most interesting applications of immersive virtual environments, as their flexibility can be exploited in order to create heterogeneous groups from all over the world who can colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…With this study, it was come out that a material designed with virtual reality had been more effective than animation and classic method. There are lots of works showing similarities with the current results (Akdemir, 2009;Arici, 2013;Aslan-Efe, 2015;Cid & Lopez, 2010;Coruh, 2011;Griol, Molina & Callejas 2014;Huang et al, 2019;Hudson, 2010;Liou & Chang, 2018;Topuz, 2018;Wu, Lee, Chang & Liang, 2013). Just like the applications of these works, the students imagined as they were in a 3D enivronment.…”
Section: Discussionsupporting
confidence: 64%
“…With this study, it was come out that a material designed with virtual reality had been more effective than animation and classic method. There are lots of works showing similarities with the current results (Akdemir, 2009;Arici, 2013;Aslan-Efe, 2015;Cid & Lopez, 2010;Coruh, 2011;Griol, Molina & Callejas 2014;Huang et al, 2019;Hudson, 2010;Liou & Chang, 2018;Topuz, 2018;Wu, Lee, Chang & Liang, 2013). Just like the applications of these works, the students imagined as they were in a 3D enivronment.…”
Section: Discussionsupporting
confidence: 64%
“…The immersive nature of VLE led to greater engagement with learning and facilitated collaborations and learning better than other learning activities. Teachers also noted greater engagement with learning and the content in general (Griol, Molina, & Callejas, 2014). An Australian study also found that combining AI and VR was effective in improving engagement and learning in younger generations.…”
Section: Ai In Higher Educationmentioning
confidence: 99%
“…A wide variety of VR studies have been conducted in various fields to design and test three-dimensional virtual environments. In this regard, an intelligent learning environment was designed to teach several subjects and conducted experiments in a Computer Science Department [73,74]. A virtual reality environment facilitates the experience of architectural spaces [75].…”
Section: Extended Reality Technology In Human Educationmentioning
confidence: 99%